Study of visual comfort in the library building based on the value of light intensity inside the room - Rasa, Barem Talang; Sativa, Sativa (Jurnal Penelitian Saintek, 2024)
This study aimed to assess the adequacy of light intensity levels in the Sragen District Library building against the standards set by SNI 03–6197–2011. The observation process began with a review of relevant lighting theories, followed by an assessment of the library spaces, field testing involving the measurement of room dimensions, and light intensity readings. The library was divided into three zones: storage, reading, and circulation. Measurement points within these zones were determined based on SNI 16–7062–2004, and light intensity was measured using a luxmeter. The results indicate that the area of openings in the building is 27.3%, which is outside the ideal range specified by SNI (10%-20%). The average light intensity in the circulation zone at 08:30 WIB is 958 Lux, while at 10:30 and 12:30 WIB, it is 118 Lux and 67 Lux, respectively. In the reading zone, the average light intensity at 08:30, 10:30, and 12:30 WIB is 218 Lux, 207 Lux, and 202 Lux, respectively. For the storage zone, the average light intensity at 08:30, 10:30, and 12:30 WIB is 119 Lux, 78 Lux, and 77 Lux, respectively. Observations reveal that none of the measured values meet the SNI standard of 300 Lux.